AN ALTERNATIVE DEVELOPMENT STRATEGY FOR COCONUT SMALLHOLDER SECTOR IN SRI LANKA - NIMAL A. FERNANDO; SUMITH de SILVA (International Coconut Community, 1988)
This paper briefly outlines several important characteristics of the coconut sector in Sri Lanka and provides a theoretical rationale for state intervention in terms of a special smallholder development strategy in the coconut sector. It points out that the current geneml development strategy of the Ministry of Coconut Industries which relies heavily on provision of development subsidies for selected capital development activities is inadequate to deal with the development problems confronted by the sector in geneml and particularly by the resource‑poor smallholders. Finally, a two‑tier development strategy is proposed for the sector with heavy focus on the smallholders with a poor resource base.